Influence of soda-lime-silica cullet on the properties of porcelain mixture - Worapong Thiemsorn (2018)
Influence of soda-lime-silica cullet on the properties of porcelain mixture was investigated. The batches were prepared with varying the recycled cullet (RC) for 0-40 wt% and fired in the range of 1,050-1,250 °C for 30 min. The properties of this porcelain with soda-lime-silica cullet were compared to traditional porcelain. Technical properties viz. apparent density, linear shrinkage, water absorption, bending strength (MOR), translucency, whiteness, microstructure and phase compositions were analyzed. The results revealed that the fired samples containing higher content of RC could vitrify at lower than 1,250 °C. The apparent density, % water absorption, % linear shrinkage, MOR and whiteness tended to decrease but the translucency was reversed with an increase of RC content at individual firing temperature. The phases and microstructures indicated the formations of mullite, quartz and amorphous phases with pores dispersed in the amorphous phase. The porcelain mixture containing 40 wt% RC was used to produce prototype products. The slip properties showed the density, viscosity and casting rate as 1.83 g/cm3, 170 mPa.s and 0.72 mm./min, respectively. The green products were fired at 1,100 °C for 30 min. The prototypes show 1.96 g/cm3 of apparent density, 7.85% of linear shrinkage, 0.08 % of water absorption, 1,218 kg/cm2 of bending strength, 73.8% of whiteness and high translucency.